Evaluasi Program Rumah Sejahtera di Kabupaten Hulu Sungai Selatan - Muhammad Sa'dudin; Ali Roziqin (Public Administration Dept, Faculty of Social and Political Science, 2024)
Implementation of the Prosperous Home Program (PRS) as an implementation of the welfare state concept in alleviating poverty and creating a livable area is the government's effort to realize the nation's prosperity. In this study, the researcher aims to comprehensively analyze and describe how the distribution of the Prosperous Home Program (PRS) grant assistance to poor communities in Hulu Sungai Selatan Regency is implemented. This research uses the method qualitative to comprehensively examine the results of the achievement of the Prosperous Home Program (PRS) without using statistics in the analysis procedure. The data collection process carried out was direct observation, structured interviews and documentation. The results of the research show that the target that the Regional Government wanted to achieve through the Hulu Sungai Selatan Regency Social Service in 2014 has been realized, by repairing around 6,077 units of uninhabitable houses by 2023. Apart from achieving the target, in its implementation there are several obstacles such as failure to provide craftsmen who have an impact on the home repair process and can influence the reporting process for the implementation of the Prosperous Home Program which results in delays in the home repair process.